Greco-Roman mineral (litho)therapeutics and their relationship to their microbiome: The case of the red pigment miltos. (December 2018) - Photos-Jones, E.; Knapp, C.W.; Venieri, D.; Christidis, G.E.; Elgy, C.; Valsami-Jones, E.; Gounaki, I.; Andriopoulou, N.C.
Abstract: This paper introduces a holistic approach to the study of Greco-Roman (G-R) lithotherapeutics. These are the minerals or mineral combinations that appear in the medical and scientific literature of the G-R world. It argues that they can best be described not simply in terms of their bulk chemistry/mineralogy but also their ecological microbiology and nanofraction component. It suggests that each individual attribute may have underpinned the bioactivity of the lithotherapeutic as an antibacterial, antifungal or other. We focus on miltos, the highly prized, naturally fine, red iron oxide-based mineral used as a pigment, in boat maintenance, agriculture and medicine. Five samples (four geological (from Kea, N. Cyclades) and one archaeological (from Lemnos, NE Aegean)) of miltos were analyzed with physical and biological science techniques. We show that: a. Kean miltos and Lemnian earth/ miltos must have been chemically and mineralogically different; b. Lemnian miltos must have been more effective as an antibacterial against specific pathogens (Gram + and Gram − bacteria) than its Kean counterpart; c. two samples of Kean miltos, although similar, chemically, mineralogically and eco-microbiologically (phylum/class level), nevertheless, displayed different antibacterial action. We suggest that this may constitute proof of microbial ecology playing an important role in effecting bioactivity and, interestingly, at the more specific genus/species level. From the perspective of the historian of G-R science, we suggest that it may have been on account of its bioactivity, rather than simply its 'red-staining' effect, that miltos gained prominent entry into the scientific and medical literature of the G-R world. Highlights: Greco-Roman mineral medicinals have a long, successful track record of being therapeutic and having diverse applications. Miltos was a prized red (iron oxide) pigment but its applications were also in medicine, agriculture and ship maintenance. Miltos is studied holistically: its mineralogy nano-fraction component, ecological microbiology and antibacterial activity. Even minor modifications in miltos ' mineral+microorganism signature can alter its bioactivity and commercial applications. We suggest that in the G-R medical/scientific literature the bioactivity of miltos was more important than its red colour.